Techniques in electromanometry of the upper esophageal sphincter - Bretan, Onivaldo [UNESP]; Henry, Maria Aparecida Coelho de Arruda [UNESP]; Cury, P. R. (My University, 1990)
The various pull-through techniques used to measure pressure and length of the upper esophageal sphincter have not been studied in depth. Because of the importance of obtaining further information about these techniques, a group of 25 dogs was submitted to upper esophageal sphincter pressure and length measurements by three different pull-through techniques (two of the continuous type and one of the station type), each with three replications per animal, to determine possible differences among techniques. A single introduction provided reliable results, with no sequential effect of the measurements or of any one technique on resting pressure. However, each technique yielded different sphincter lengths, higher values being obtained when the continuous techniques were used.
Keywords: animal experiment; diagnosis; dog; esophagus; lower esophagus sphincter; male; manometry; methodology; priority journal; Animal; Comparative Study; Dogs; Esophagogastric Junction; Male; Manometry